Issues in the developmental approach to mental retardation - Hodapp, Robert M.; Burack, Jacob A; Zigler, Edward 1930-2019 (Cambridge University Press, 1990)
Issues in the Developmental Approach to Mental Retardation is one of the first books exclusively devoted to applying the theories, findings and approaches used in work with nonretarded children to several types of retarded individuals. The editors and contributors define the developmental approach and explore theoretical issues as they relate to retarded populations. Problems involving similar sequences of development, cross-domain relations, the environment, and motivation are all discussed, as is the importance of separating the various etiological groups for research and intervention purposes. The contributors also examine the nature of development in specific etiological groups; types of retardation that are addressed include: cultural-familial retardation, Down syndrome, fragile X syndrome, autism, and children with sensory and motor handicaps. This significant volume demonstrates how data from nonretarded development can inform work with retarded populations and how findings from children with mental retardation enrich developmental theory